ECONOMIC VALUE OF CRITICAL LAND IN SEMPAYANG VILLAGE, NORTH KALIMANTAN - Sulistya Rini Pratiwi; Yohanna Thresia Nainggola; Meylin Rahmawati (Journal of Applied Economics in Developing Countries, 2024)
This research aims to identify the locations of vulnerable critical land areas and assess the economic value of mitigating agricultural land in critical conditions within Sempayang Village, North Kalimantan, Indonesia. The study employs Geographic Information Systems (GIS) to analyze land distribution and the Contingent Valuation Method (CVM) to estimate the economic value. A purposive sampling method was used to select 51 respondents from local farmers, with a focus on their willingness to pay for land rehabilitation. The results of this research are the largest critical land area was found in Malinau District, covering 54,108 hectares. Farmers showed a willingness to pay between Rp. 26,000 and Rp. 30,000 for land rehabilitation efforts, with a total economic value of Rp. 45,360,000 annually for non-critical land. The study underscores the importance of community and government collaboration for effective land restoration programs.